2008
DOI: 10.1007/s11418-008-0304-6
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the antispasmodic effect of shakuyaku-kanzo-to (TJ-68), a Chinese herbal medicine, on the duodenal wall by direct spraying during endoscopic retrograde cholangiopancreatography

Abstract: The purpose of the study was to evaluate the suppressive effect of TJ-68 on duodenal spasms during endoscopic retrograde cholangiopancreatography (ERCP). At the point when the duodenal papilla was confirmed after insertion of the endoscope during ERCP, 5.0 g TJ-68 (Tsumura Co., Tokyo, Japan) was dissolved in 50 ml of saline at 36 degrees C, and the whole volume was sprayed slowly using a spray tube from the orifice of the forceps to the duodenal papilla of the 50 patients who demonstrated peristalsis of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…We previously reported at the Japan Digestive Disease Week 2006 that duodenal peristalsis was inhibited by directly spraying TJ-68 solution onto the duodenum during ERCP. Sakai et al [26] later confirmed this finding, reporting that TJ-68 inhibited duodenal spasm during ERCP. These effects were observed because TJ-68 in Glycyrrhizae radix inhibits acetylcholine-induced contraction of the smooth muscle and Paeoniae radix inhibits neurogenic contraction.…”
Section: Discussionmentioning
confidence: 80%
“…We previously reported at the Japan Digestive Disease Week 2006 that duodenal peristalsis was inhibited by directly spraying TJ-68 solution onto the duodenum during ERCP. Sakai et al [26] later confirmed this finding, reporting that TJ-68 inhibited duodenal spasm during ERCP. These effects were observed because TJ-68 in Glycyrrhizae radix inhibits acetylcholine-induced contraction of the smooth muscle and Paeoniae radix inhibits neurogenic contraction.…”
Section: Discussionmentioning
confidence: 80%
“…In a previous observational study [9], Shakuyakukanzoto acted as an anti-spasmodic agent and abolished duodenal peristalsis in the majority of participants to whom it was administered, but this was not a randomised, controlled study and the extent of suppression of peristalsis was not measured. In this study, we excluded participants in whom duodenal peristalsis was not evident at duodenoscopy, and assessed peristalsis and its influence on the technical difficulty of cannulating the common bile duct using the scoring system previously described by Niwa et al [11].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size calculation for this study was based on the effective rate achieved in a previous trial, with the response rates in the Shakuyakukanzoto and control groups expected to be 70 and 10%, respectively. The no-peristalsis rate was expected to be 40% [9, 13]. The target sample size required to detect a difference in the response rate between the groups with a significance level of 5% and a power 90% was 13 per group, including a 40% dropout rate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shakuyakukanzoto, a Kampo prescription consisting of Glycyrrhiza Root and Peony Root, has been well-known among primary care doctors in Japan for having an immediate relieving effect on muscle cramps [5, 36], which has been proven by several open-labeled trials in hemodialysis patients [46, 47]. Shakuyakukanzoto also has a significant suppressive effect on duodenal spasms during endoscopic retrograde cholangiopancreatography [48]. Taken together, the combination of Glycyrrhiza Root and Peony Root seems to have an antispasmodic pain-relieving effect on both skeletal and smooth muscle.…”
Section: Discussionmentioning
confidence: 99%